Health promotion and prevention of risks and diseases in Supplementary Health: a brief history - Kátia Audi Curci; Martha Regina de Oliveira; Michelle Mello de Souza Rangel; Simone Mendes (O Mundo da Saúde)
The development of programs for the promotion of health and prevention of diseases and risks aims the advisable identification and monitoring of health risks, the reduction of morbidity rates in old people and the improvement of quality of life of beneficiaries of private health care, since the majority of diseases affecting the population is preventable. As an offshoot of the Regulatory Agenda from ANS (National Agency for Supplementary Health), a working group with representatives from the ANS, the Academy, operators and providers of health services was formed to discuss the process of active aging throughout a life course and propose mechanisms to encourage membership of beneficiaries in programs for health promotion and prevention of risks and diseases. Furthermore, the process of Regulatory Impact Analysis (RIA) was done. The need to develop a normative instrument for defining the concepts related to health promotion and the scope of programs modeling was highlighted. Until August 2011, prior to the publication of the Regulatory Resolutions no. 264 and no. 265, ANS had a databank of 127 approved programs, with an estimated participation of 198 000 beneficiaries. After eleven months of the term of the new regulations, there were a total of 750 programs reported in the ANS, with a participation projection of 1.12 million beneficiaries, which represented an increase of nearly five times the number of users of health care benefiting from the initiative. The programs have focused on activities aimed at encouraging physical activity, healthy eating and prevention of smoking and diseases such as cancer, sexually transmitted illnesses, osteoporosis, hypertension, diabetes, obesity. Another area focused is health of old people. ANS has further developed strategies to influence Programs for Health Promotion and Prevention of Risks and Diseases taking into account the specificities of the supplementary sector and at the same time the policies undertaken by the Ministry of Health. Strategies adopted intend to introduce health promotion and prevention of diseases into the context of a care plan integrated to other actions and complexities of services, promoting therefore health management qualification in order to improve the quality of life of private health care beneficiaries.